Lifestyle Intervention Strategies to Maintain Cognitive Health in Middle-aged Adults: A Scoping Review - CVR Abimanyu; Aisyah Kamila (Journal Research of Social Science, Economics, and Management, 2025)
Cognitive decline in middle-aged adults (40–60 years old) represents a significant public health challenge with implications for quality of life and dementia prevention. The research problem centers on the limited attention given to this critical age group compared to elderly or adolescent populations, despite this being a crucial transition period during which preventive interventions can have maximum impact. This study aims to map lifestyle intervention strategies to maintain the cognitive health of this age group. The method used was a scoping review based on PRISMA-ScR, with literature from Scopus, PUBMED, and SpringerLink. Of the 94 articles found, 11 met the criteria for analysis. The results showed that a healthy diet, physical activity, cognitive stimulation, social interaction, as well as management of physical conditions such as chronic pain and frailty, were effective in slowing down the decline in brain function. The multidomain approach and personalization through shared decision-making have proven to be more optimal than a single strategy. In conclusion, healthy lifestyle interventions in middle-aged adults play an important role in preventing dementia and improving quality of life; therefore, they need to be integrated into public health programs.